Tetrahedral Space-Time Elements in the Analysis of Forced Vibrations of Plates - Kotulecki, J.; Witkowski, M. (Engineering Transactions, 1988)
The paper presents a generalization of the space-time element method with a triangular net. Space-time is three-dimensional in dynamic analysis of plates, so instead of the triangular elements, tetrahedrons were used. The space-time tetrahedral element of a moderately thick plate was produced and examined. The advantages of a triangular net, especially those leading to equations uncoupled with respect to then, were conserved.